Animal Tales in Cherokee and Sumbawa Tradition: A Study on Cherokee and Sumbawanese Values Reflected in Three Pairs of Stories - , Vivin Nila Rakhmatullah, Prof. Djuhertati Imam Muhni, M.A., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
United States is a nation that composite of many peoples and consists of various ethnic groups whose origin came from many different parts of the world. Their folklores enrich and contribute the American experience. Indonesia also a nation that composite of many peoples and consists of various ethnic groups whose origin lives in Indonesian archipelago. Therefore this thesis observes a comparative study of animal tales of Cherokee, one of Native American tribes and Sumbawa, an Indonesia tribe. The objectives of the study are to explain the similarities and the differences in delivering moral values between the three pairs of tales, to explore the cultural values in Cherokee and Sumbawa animal folktales, and to elucidate the representation of the characters in those animal folktales. Employing multidisciplinary theories under American Studies those are âstructuralismâ by Alan Dundes and âmicro to macroâ by Leo Marx. By conducting qualitative research, it is acknowledged that the cultural product (microcosm) that is folktales in form of animal tales is a reflection of the empirical life (realities) of the society that gives birth to it (macrocosm). These three pair of animal tales reflected the realities of Cherokee and Sumbawa society. The animal tales of Cherokee are How The Terrapin Beat The Rabbit, The Rabbit and The Possum Seek A Wife, and How The Deer Got His Horns. While the animal tales of Sumbawa are: The Tales of The Monkey, The Turtle and The Snail, The Tales of The Monkey And The Flamingo and The Cocky Monkey (Sruduk Team). Animal tales in both tribes are using animal characters to represents human being, their characteristics, moral and cultural values. Their main characters in most of animal tales are different